PERAN UNIT PENEGAKAN HUKUM SATPOL AIRUD TERHADAP TINDAK PIDANA PENGGUNAAN BOM IKAN OLEH NELAYAN DI PERAIRAN LAUT TELUK BAUBAU - Samaluddin Samaluddin; Afdal Rahmat Slamat (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
This study aims to determine the role of the Satpolairud law enforcement unit against the crime of fishing bombing and to find out the obstacles faced by Satpolairud law enforcement in efforts to overcome the use of fish bombs by fishermen in the sea waters of Baubau Bay. The results of the study concluded that the Satpolairud Polres Baubau in dealing with criminal acts of fishing with peleak materials is to carry out routine patrols in the waters of Baubau bay and provide education to coastal communities about ecosystems in water areas. The obstacles faced are the lack of Satpolairud personnel, the lack of human resources for law enforcement officers and the lack of adequate facilities and infrastructure as supporting factors in carrying out supporting factors in carrying out patrol duties.